Primary exocrine pancreatic insufficiency in children (a clinical case of Shwachman-Diamond syndrome) - V.S. Berezenko; Yu.I. Proshchenko; Kh.Z. Mykhayluk; M.B. Dyba; O.M. Tkalik; Yu.O. Savenko (Zdorovʹe Rebenka)
The purpose of the article is to increase the vigilance of clinicians in various fields of medicine to Shwachman-Diamond syndrome in children and to raise awareness of its clinical manifestations, diagnosis and treatment using the example of the case study. An empirical, descriptive study of a clinical case of Shwachman-Diamond syndrome in a child was conducted. In addition, the literature data from PubMed, Medscape, and CDC were analyzed. Shwachman-Diamond syndrome is an autosomal recessive disease characterized by absolute exocrine pancreatic insufficiency and is the second most common form of primary exocrine pancreatic insufficiency. The diagnosis is made in the presence of a characteristic combination of exocrine pancreatic function disorders, hematologic manifestations (neutropenia, thrombocytopenia, anemia), skeletal abnormalities and is confirmed by molecular genetic testing (mutation in the SBDS gene, which is localized on 7q or 11 and inversion of the 9th chromosome pair). Early diagnosis and timely treatment prevent the onset of adverse symptoms and disability. Treatment is complex and syndromic and includes dietary therapy, enzyme replacement therapy, supplementation with fat-soluble vitamins and correction of hematologic disorders.